7+3(2x-1)=

Simple and best practice solution for 7+3(2x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3(2x-1)= equation:


Simplifying
7 + 3(2x + -1) = 0

Reorder the terms:
7 + 3(-1 + 2x) = 0
7 + (-1 * 3 + 2x * 3) = 0
7 + (-3 + 6x) = 0

Combine like terms: 7 + -3 = 4
4 + 6x = 0

Solving
4 + 6x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + 6x = 0 + -4

Combine like terms: 4 + -4 = 0
0 + 6x = 0 + -4
6x = 0 + -4

Combine like terms: 0 + -4 = -4
6x = -4

Divide each side by '6'.
x = -0.6666666667

Simplifying
x = -0.6666666667

See similar equations:

| 7-3(2x-1)= | | y^2-8y=4 | | 7+3(2x-1)=2x+26 | | y^2-2x=24 | | 3x+2y+4z=20 | | 6.03x-13.58x= | | 7(x+3)=5x+23 | | 6w+11=120 | | 2/5*7/8=7/15 | | 2y+5x-4=0 | | (x-1)(x+4)(x+5)=84 | | 2x+69=3 | | 8+21x=5+12x | | 8x+21x=5x+12x | | 9s-44=2s+26 | | 2x+54=154 | | x-8=(-1/4)y+48 | | p-8=(-1/4)x+48 | | 12x^2+29-8=0 | | 3m+17=7m+19 | | p=(1/4)x+48 | | 47+5/12b=100 | | 66-6x=21x+24 | | TC=10+5Q | | 3.92/0.8 | | 12x-4y=0 | | 3x=45+2x | | 2a(3d+2)= | | 6.0x-20=20 | | 72(8/12x)-106(-17-8) | | 53+2x=x+111 | | 10y+y^10=1100 |

Equations solver categories